2009
DOI: 10.1111/j.1524-4725.2009.01072.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Orlistat on Visceral Fat After Liposuction

Abstract: Visceral fat does not decrease despite weight loss after liposuction. Orlistat use postliposuction might be a useful tool because it shows a tendency to reduce visceral fat and improve blood lipids profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Last but not the least, reviewing the literature we identified studies, which could have been included, at least at the systematic review, such as those from Robles-Cervantes et al to Montoya et al which fulfill the inclusion criteria described herein [4,5]. This fact seems to limit the validity and reliability of the review, and thus its results.…”
mentioning
confidence: 95%
“…Last but not the least, reviewing the literature we identified studies, which could have been included, at least at the systematic review, such as those from Robles-Cervantes et al to Montoya et al which fulfill the inclusion criteria described herein [4,5]. This fact seems to limit the validity and reliability of the review, and thus its results.…”
mentioning
confidence: 95%
“…Based on the idea that visceral fat has deleterious effects on metabolism, surgical removal of visceral fat was proposed to be a way forward in achieving lower visceral adiposity. However, removal of visceral fat alone does not provide metabolic advantages2728, possibly because visceral fat is highly mobilized. Although fat transplantation involving donor and recipient mice has been carried out earlier324, we raised the question: Does autologous transplantation of visceral fat to sub-cutaneous region offer metabolic advantage?…”
mentioning
confidence: 99%
“…Otherwise, a stable nutritional biochemical pattern was documented throughout the observation period (Table 2). Table 3 summarizes the findings from the literature concerning the impact of liposuction and abdominoplasty on metabolic variables [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…Alleviation of systemic inflammation and insulin resistance has been reported by some researches, whereas in certain studies, the improvement of plasma lipids has been confirmed [4][5][6][7][8]. In contrast, no changes in insulin action and cardiovascular risk factors have been noticed by other studies [9,10].…”
Section: Introductionmentioning
confidence: 85%